Walking the Talk: Opportunities for Nepali Businesses to be Ethical and Socially Responsible - Bhandary, Ashok (Kalika Journal of Multidisciplinary Research, 2023)
High performing businesses around the world have realized that business ethics, and more specifically ethical business culture is central to competing and performing effectively in the market. Being ethical and responsible necessitates firms to fulfill all their responsibilities towards stakeholders. Unfortunately, Nepali businesses have fallen short of their obligations. In line with this, the purpose of the study is to examine the status quo on ethics and social responsibility for Nepali businesses. Methodology utilized includes empirical scrutiny of both qualitative and quantitative data. Data from multiple sources also point to the fact that Nepali institutions generally lag far behind their peers in promoting a culture of ethics. Based on scrutiny of the largest Nepali banks, this article makes the sober finding that Nepali businesses have talked the talk on ethics and responsibility, but have failed to translate much of that talk into action. More specifically, top management teams (TMTs) say endearing things on corporate social responsibility that is not followed through with CSR actions downstream. Although the implication of this study is primarily towards Nepal’s banks, it can easily extend to other Nepali businesses with similar business culture. Therefore, it is high time that Nepali businesses ingrain ethics and responsibility into their culture so that they too can minimize missed opportunities and become serious contenders in this competitive world.